Seismic vulnerability assessment of a high-rise molten-salt solar tower based on incremental dynamic analysis - Sun Weiwei; D’Ayala Dina; Fu Jinxing; Gu Wentao; Feng Jun (E3S Web of Conferences, 2020)
This paper investigates the seismic performance of a high-rise molten-salt solar tower by finite element modelling. The integrated and separated models for solar tower based on the concrete damage plastic model are validated by matching the behaviour of similar reinforced concrete chimney specimens. The modal analysis demonstrates the first four modes of the solar tower are translational vibration. Seismic simulations are developed through the incremental dynamic analysis. The most disadvantageous position of the tower is all concentrated in the opening section under multidirectional seismic excitations. The top displacement of the tower under bidirectional and three-directional earthquake actions is larger than that under unidirectional earthquake actions. The results of the seismic vulnerability assessment show that when the PGA equals to 0.035g, the tower will be intact; when the PGA equals to 0.1g (design peak ground acceleration), the probability of the moderate damage state is within 1.5%; when the PGA equals to 0.22g (maximum considered earthquake), the probability of the destruction state is below 0.7%. The seismic partitioned fragility analysis of the tower under multidirectional earthquake excitations illustrates that there are two peaks in the vulnerability surfaces. The anti-collapse analysis indicates the tower has a good seismic performance under multidirectional seismic excitations.